(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Generalized periodontitis is the most common inflammatory periodontal disease. Currently, it can be concluded that the local mechanisms of periodontitis development have been largely deciphered. At the same time, periodontitis is considered not only as a localized periodontal inflammation caused by the microflora of dental plaque, but also as a whole-body response to bacterial infection. On the other hand, it is clear that systemic processes play a significant role in the pathogenesis of generalized periodontitis, leading to profound changes in the body’s internal environment and, consequently, to structural damage to periodontal tissues.